Current Perspectives on the Use of Meditation to Reduce Blood Pressure. (5th March 2012) - Goldstein, Carly M.; Josephson, Richard; Xie, Susan; Hughes, Joel W.
Abstract : Meditation techniques are increasingly popular practices that may be useful in preventing or reducing elevated blood pressure. We reviewed landmark studies and recent literature concerning the use of meditation for reducing blood pressure in pre-hypertensive and hypertensive individuals. We sought to highlight underlying assumptions, identify strengths and weaknesses of the research, and suggest avenues for further research, reporting of results, and dissemination of findings. Meditation techniques appear to produce small yet meaningful reductions in blood pressure either as monotherapy or in conjunction with traditional pharmacotherapy. Transcendental meditation and mindfulness-based stress reduction may produce clinically significant reductions in systolic and diastolic blood pressure. More randomized clinical trials are necessary before strong recommendations regarding the use of meditation for high BP can be made.